Stretchable wideband dipole antennas and rectennas for RF energy harvesting. (May 2021) - Zhu, Jia; Hu, Zhihui; Song, Chaoyun; Yi, Ning; Yu, Zhaozheng; Liu, Zhendong; Liu, Shangbin; Wang, Mengjun; Dexheimer, Michael Gregory; Yang, Jian; Cheng, Huanyu
Abstract: The ultimate application of bio-integrated, stretchable electronics hinges on the indispensable modules of stretchable wireless data transmission and power supplies. While radiofrequency (RF) antennas and rectennas could enable wireless communication and RF energy harvesting in the far-field, their performance deteriorates because of the frequency detuning from mechanical deformations. Here, stretchable wideband antennas and rectennas are introduced to robustly operate and combine received RF power over their wideband upon mechanical deformations. Devices with stretchable wideband antennas and rectennas create application opportunities such as self-powered systems, remote monitoring of the environment, and clean energy. A comprehensive set of manufacturing schemes, device components, and theoretical design tools for the stretchable wideband antennas and rectennas is reported. A stretchable wideband rectenna integrated with various functional sensing modules and its demonstration with enhanced effective efficiency over the state-of-the-art by 10–100 times illustrates a system-level example of this technology. Graphical abstract: All-LIG stretchable electronics composed of various sensing modules and antennas fabricated by a simple laser scribing for potential self-powering and remote sensing. High RF energy harvesting efficiency based on the stretchable wideband dipole antenna from the ambient environment was achieved even upon mechanical deformations or being attached to the jacket. Image 1 Highlights: All-LIG stretchable electronics with sensors and antennas fabricated by the simple laser scribing. Stretchable wideband dipole antennas composed of two pairs of serpentine arms. Stretchable wideband dipole rectennas for ambient RF energy harvesting upon various deformations. Non-degraded RF energy harvesting performance in wearable applications.